EXPLORING THE IMPLEMENTATION OF IN-SERVICE TRAINING PROGRAM: A CASE STUDY IN PUBLIC ELEMENTARY SCHOOLS - Gape, Hadassah Salem (Journal of Arts & Social Sciences, 2025)
This study explores the Implementation of In-Service Training Program In-service training (INSET) in public elementary schools.  It utilized multiple case study which is a valuable approach and employed triangulation through interview, focus group discussion and observation. Themes and sub-themes were generated from the interviews conducted for this research. In the statement of the problem 1 on the school administrators’ response, the theme is Maximizing Team Performance through Collaboration, Professional Development and Support, the sub themes are: (1) Collaboration and Teamwork, (2) Professional Development, and (3) Training Support. In the statement of the problem 2 on the teachers’ response, the theme is on Strategic Conduct of Activities to Optimize Organizational Performance for Training and Development, the sub themes are: (4) The school head did a systematic needs assessment, (5) Communication strategies were done, (6) The school head made an effective facilitation of training and workshops, and (7) Planning and Coordination of Training and Development Activities. In the statement of the problem 2 on the teachers’ response, the theme is the Teachers Found Contentment and Appreciation in the Process of Acquiring New Information and Skills Despite the Constraints of Limited Resources and Time, the sub themes are: (8) The Teachers are Mentored through the Activities during the INSET, (9) The Teachers are Contented and Appreciates the Process of Acquiring New Information and Skills, (10) Limited Resources and Lack of Ample Time, and (10) The Teachers Felt the Struggle in Accomplishing the Activities. These findings highlight the need for a contextually relevant, school-based INSET enhancement plan that addresses these constraints and optimizes the effectiveness of professional development for public elementary school teachers.